Self-similarity and synthetic biology: a possible fractal anticipation - Robert Meckin (Journal of Responsible Innovation)
In the field of synthetic biology, a promissory technoscience, researchers use risk-based and speculative scenarios to anticipate synthetic biology futures. Yet, there is a sense in the field of history repeating as synthetic biologists repeatedly deal with similar challenges. Perhaps a focus on contemplating the unexpected and attempts to deal with complex futures comes with a failure, paradoxically, to prepare sufficiently for the expected. This study develops a conceptual framework derived from fractals and analyses data from ethnographic involvement in the field synthetic biology to reimagine how patterns in synthetic biology practices repeat at different orders of scale. This study begins with the ‘pressure testing’ of a biofoundry and shows how synthetic biology repeats at different scales of organisation, interaction and time. The case is made for a possible fractal anticipation which would have the capacity to identify patterns and support innovators, social scientists and researchers to be better prepared for encountering similar developments at different orders of magnitude.